RAPID CARDIO TROPONIN-T ASSAY IN PERICARDIAL FLUID FOR POST MORTEM DIAGNOSIS OF SUDDEN MYOCARDIAL INJURY: A CASE CONTROL STUDY (Journal of Forensic Medicine & Toxicology, 2021)
Background: Troponin T, a myofibrillary protein, is a constituent of the contractile apparatus of skeletal and cardiac muscle. Cardiac Troponin T (cTnT) concentration is raised in cases of myocardial injury. Rapid cTnT is routinely used in clinical settings to assess myocardial injury. Limited available literature on postmortem assessment of cTnT in pericardial fluid and blood suggest that its levels are raised in cases of sudden cardiac deaths (SCD) and electrocution. Keeping in view of the above a validation case control study was designed and executed with primary objective to ascertain cases of myocardial injury (SCD and electrocution [Test group]by a rapid cTnT in pericardial fluid on medico-legal postmortem examination and compare them with other non-cardiac causes of death [Control group]. Result: Rapid cTnT test from pericardial fluid was found positive in 35 (87.5%) cases in Test group and 32 (91.4%) cases in Control group. On comparison of the two groups by Chi-Square test it was found insignificant (P value=0.716).
Keywords: Cardiotroponin T; Sudden Myocardial Injury; Pericardial Fluid; Postmortem; Case Control study.